The study of internal structure of woven glass and carbon fiber reinforced composite materials with embedded fiber-optic sensors (Fracture and Structural Integrity, 2019)
In this work, samples from composite materials with embedded optical fibers are investigated. It is known that for unidirectional layered composite materials, under certain conditions, a distortion of the internal structure and the formation of such technological defect as resin pocket in the region of the embedded optical fiber occur. So it is important to evaluate the change in the internal structure for other types of reinforcement, in particular, woven reinforcement. Analysis of the internal structure of the studied materials with 2´2 twill weave style was carried out using a digital microscope. In addition, the reflected optical signal from the Bragg gratings after being embedded into the composite material is analyzed.
Keywords: Polymer composite material; woven reinforcement; single-mode optical fiber; FBG; sensor embedded in the material